One new genus and four new species of Tegonotini (Acari: Eriophyidae) from Guangxi, South China - Wei, Suigai; Wang, Guoquan; Qin, Aizhi (Zootaxa, 2009)
One new genus and four new species of the tribe Tegonotini (Eriophyidae: Phyllocoptinae) from Guangxi Zhuang Autonomous Region, China are described and illustrated: Asetidicrothrix luculiae gen. nov. and sp. nov. infesting Luculia sp. (Rubiaceae), Phyllocoptacus aporusae sp. nov. infesting Aporusa chinensis (Champ.) Merr. (Euphorbiaceae), Shevtchenkella acer sp. nov. infesting Acer davidii Franch. (Aceraceae) and Tegophyes embelia sp. nov. infesting Embelia oblongifolia Hemsl. (Myrsinaceae). All species described here are vagrants on the undersurface of host leaves. A key to the genera of Tegonotini from China is provided.